Sistem Pendukung Keputusan Penerima Bantuan Pada Desa Anduhum Menggunakan Metode SAW - Munjiati, Annisa; Rafi'i, Muhammad; Purbiyanto, Eko (Indonesian Journal of Information Technology and Computing (IMAGING), 2024)
Help Village Fund Cash Direct or abbreviated is the provision of cash to poor or incapacitated families in villages originating from the Village Fund with the aim of accelerating the elimination of extreme poverty and reducing economic impact. The decision support system for beneficiaries in Anduhum Village uses the Simple Additive Weighting method (SAW) is a system designed to assist officials in determining the most suitable beneficiary candidates based on predetermined criteria, such as income, number of dependents, health conditions, and educational status. The SAW method is used to calculate the weight of each criterion and produce a ranking of beneficiary candidates who best meet these criteria. This system is expected to increase efficiency and effectiveness in distributing aid in Anduhum Village. The development of this decision support system was developed using the SAW method using the PHP programming language (PHP: Hypertext Preprocessor), as well as a MySQL database as a database server. From the results of calculations using the SAW method, recommendations for the names of beneficiaries of social assistance programs are obtained based on ranking. Besides that, based on the results of blackbox testing , this system runs according to its function